Massive rhizobial genomic variation associated with partner quality in Lotus–Mesorhizobium symbiosis. Issue 12 (5th October 2020) - Bamba, Masaru; Aoki, Seishiro; Kajita, Tadashi; Setoguchi, Hiroaki; Watano, Yasuyuki; Sato, Shusei; Tsuchimatsu, Takashi
ABSTRACT: Variation in partner quality is commonly observed in diverse cooperative relationships, despite the theoretical prediction that selection favoring high-quality partners should eliminate such variation. Here, we investigated how genetic variation in partner quality could be maintained in the nitrogen-fixing mutualism between Lotus japonicus and Mesorhizobium bacteria. We reconstructed de novo assembled full-genome sequences from nine rhizobial symbionts, finding massive variation in the core genome and the similar symbiotic islands, indicating recent horizontal gene transfer (HGT) of the symbiosis islands into diverse Mesorhizobium lineages. A cross-inoculation experiment using 9 sequenced rhizobial symbionts and 15 L. japonicus accessions revealed extensive quality variation represented by plant growth phenotypes, including genotype-by-genotype interactions. Variation in quality was not associated with the presence/absence variation in known symbiosis-related genes in the symbiosis island; rather, it showed significant correlation with the core genome variation. Given the recurrent HGT of the symbiosis islands into diverse Mesorhizobium strains, local Mesorhizobium communities could serve as a major source of variation for core genomes, which might prevent variation in partner quality from fixing, even in the presence of selection favoring high-quality partners. These findings highlight the novel role of HGT of symbiosis islands in maintaining partner quality variation in the legume–rhizobia symbiosis. Abstract : Through full-genome sequencing of rhizobial bacteria and a cross-inoculation experiment with its associated plants, this study investigated the genetic basis of rhizobial quality in the nitrogen-fixing symbiosis.